Character and Student Ability of Covid-19 Understanding in Digital Era in 2020 - Allif Syahputra Bania; Nuraini Nuraini; Maria Ulfa (Budapest International Research and Critics University, 2020)
The purpose of this research is to describe the character of students towards the understanding of Covid-19 in the digital age, to describe the ability of students to translate understanding of terminology relating to Covid-19 in the digital age, and to describe the effectiveness of digital campus on understanding covid-19 by students in the digital age. The data analysis technique in this research is quantitative descriptive. The result shows that The ability of students to translate intralingually new words that were present during the Covid-19 period is very good and dominant in number. The dominant character of students in putting an interest in the knowledge, learning and translation of new words during the Covid-19 pandemic to deal with the spread of Covid-19 was very good, interested, uplifting and enthusiastic. The level of effectiveness of digital campuss by students when the corona pandemic is very high and dominant. Thank you to the LPPM & PM Universitas Samudra from the DIPA 2020 funds and all those who assisted our research activities so that we can complete the flagship basic research.